The mitochondrial genome of a leaf insect Phyllium westwoodii (Phasmatodea: Phylliidae) in Southeast Asia. Issue 3 (4th March 2021) - Dong, Zhiwei; Li, Jun; He, Jinwu; Liu, Guichun; Mao, Chuyang; Zhao, Ruoping; Li, Xueyan
Abstract: The nearly complete mitochondrial genome (mitogenome) of Phyllium westwoodii, a typical leaf mimic insect in Phasmatodea, was obtained in this study. This mitogenome is 17, 222 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs) and almost complete control regions. All PCGs initiate with 'ATN' except for NAD4L that uses 'TTG' as the start codon, and terminate with 'TAA' except for COX2 that uses a single 'T' residue as the stop codon. The phylogenetic analysis based on the concatenated sequences of 13 PCGs and two rRNAs shows that P . westwoodii is closer to Phyllium tibetense than Phyllium giganteum .